Upaya Peningkatan Prestasi Belajar IPA materi Sistem Pernafasan melalui Penerapan Model Pembelajaran Kooperatif dengan Metode Talking Chips pada Siswa kelas VIII MTs Imam Al Ghozali Panjerejo Kecamatan Rejotangan - Daroini, Muh (Center of Education Journal (CEJou), 2022)
Based on the observations, it is known that the VIII grade students of MTS Imam Al Ghozali Panjerejo Tulungagung in science subjects still use the lecture method. In addition, learning is still not active and this also has an impact on low student achievement. The KKM standard for science subjects is 75. Before the action, it was known that only 55% of students completed with an average score of 56.78. The purpose of this study is to improve the results of student achievement in science subjects with material on the respiratory system by applying the talking chips method of cooperative learning. This research design uses classroom action research (CAR) using 2 cycles. In each cycle there are 4 stages such as planning, action, observation and reflection. The results showed that the application of the cooperative learning model with the talking chips method could improve the learning achievement of class VIII students of MTS Imam Al Ghozali Panjerejo, Rejotangan District in science subjects on respiratory system materials.